A marcha humana: uma abordagem biomecânica - A. Sousa (2010)
The biomechanical analysis of gait involves, among others, kinematic, kinetic and electromyographic signals, which, together, allow describing the gait phenomenon. This paper reviews studies focusing on the biomechanical aspects of gait, in order to understand which components must be considered in that analysis and the models supporting experimental findings. The analysis performed showed that the need to redirect the center of mass speed between steps predicts a strong component of energy expenditure in gait and that this is associated with speed.